Association of acute vestibular/ocular motor screening scores to prolonged recovery in collegiate athletes following sport-related concussion. (11th May 2020) - Whitney, Susan L.; Eagle, Shawn R.; Marchetti, Gregory; Mucha, Anne; Collins, Michael W.; Kontos, Anthony P.; ,
ABSTRACT: Introduction: Researchers have yet to explore the association of acute (i.e., within 3 days) post-injury VOMS scores and length of time until clearance to return to play in collegiate athletes. Objective: The purpose was to determine if individual Vestibular/Ocular Motor Screening (VOMS) component symptom scores (e.g., smooth pursuits, convergence, vestibular-ocular reflex) can predict clearance to return to activity from a sport-related concussion. Methods: Pre-season demographic and medical history and post-injury VOMS testing were collected (n = 79) on collegiate student-athletes following concussion. Impaired vestibulo-ocular function post-injury scores (≥2) were compared to normal scores using survival analysis, with days to clearance to return to sport as the outcome. Results: Abnormal scores on smooth pursuits ( p =.026), horizontal saccades ( p =.025), vertical saccades ( p =.028), and convergence ( p =.031) were associated with lower probability of clearance in comparison with normal scores. Any score ≥2 predicted significantly greater days to clearance for return to play (13.1 days; 95% CI: 11.9–14.3; p = .025) compared with athletes with no abnormal test scores (9.6 days; 95% CI: 7.2–12.1, P =.014). Discussion: Post-injury symptoms with VOMS smooth pursuit, saccades, and convergence is associated with increased time-to-clearance for return to sport in collegiate athletes.